Small African Economies in a More Uncertain Global Trade Environment : The Potential Impact of Post-AGOA Scenarios for Lesotho - Maliszewska, Maryla; Engel, Jakob; Arenas, Guillermo; Kotschwar, Barbara (World Bank, Washington, DC, 2019)
This paper provides a forward-looking view of trade and its relevance for Lesotho’s medium- and long-term development. It does this through computable general equilibrium analysis of potential impacts based on specific trade-related scenarios. The scenarios include the potential loss of American Growth and Opportunities Act preferences and preference erosion against competitors through, for example, a United States–Vietnam Free Trade Area. An immediate loss of American Growth and Opportunities Act preferences would have a significant economic impact that far exceeds that of a potential future United States–Vietnam Free Trade Area. If these preferences were suspended in 2018, Lesotho would face a loss of 1 percent in income by 2020, relative to the baseline, and exports of textiles and apparel would drop by 16 percent. The computable general equilibrium simulations stress the need to strengthen efforts to support structural transformation leading to diversification of export products and markets, improving backward and forward linkages, and lowering trade costs. The simulations also indicate that trade facilitation measures leading to an average decrease in trade costs of 2 percent per year would eliminate the negative consequences of the loss of American Growth and Opportunities Act preferences in terms of the loss of income. The changing external environment is likely to offer new opportunities to Lesotho's export industries in the medium term, including through regional integration under the Continental Free Trade Area.